A SURVEY OF 100 HEALTHY INDIVIDUALS IN TEHRAN FOR BLOOD GLUCOSE, UREA, URIC ACID, AND CHOLESTEROL - R. Mokhtar Massoumi (Tehran University of Medical Sciences, 1975)
There have been no statistical findings published on normal levels for glucose, urea, uric acid, and cholesterol in Iran. This is an attempt as a pilot project, to look into the matter. For this purpose one thousand healthy individuals consisting of 333 Females and 667 males of mixed age group were tested by an automated method (Technicon SMA), and a manual method (Bio Medic diagnostic kits) for the above mentioned parameters. Normal range (two standard deviations) was calculated for each parameter. A comparison of calculated normal value with statistical findings (1, 2, 3, 4, 5, 6, 7) show the same ranges for glucose, urea, and cholesterol. For uric acid our calculated normal range in males and females was from 18.6% to 44.44% higher than other statistical findings for the same parameter with higher values in males than females. This could be due to several factors such as diet, race and elevation in Tehran area where the survey was conducted, High elevation would result higher hemoglobin and RBC which causes higher turnover of RBCs which in turn liberates more purin compounds and finally uric acid as a purin metabolite. It would be desirable to conduct similar statistical work-up in different parts of Iran with lower and higher elevation to further evaluate this point. It would also be desirable to conduct a more detail study on different age and sex groups to classify the normal range for cholesterol according to age and sex.